Anak Berhadapan Hukum Dalam Perspektif Restorative Justice - Pristiwiyanto, Pristiwiyanto (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2020)
Children are the mandate and blessings of God Almighty, which is inherent in their dignity and dignity as whole human beings. A country representing an institution / institution that is responsible for meeting the financial needs of its people should be able to make a budget that can realize the protection and welfare of children in the form of good health protection from philosophical aspects, right from sociological aspects, and correct from normative aspects of solving and protection of children in conflict with the law. Children who are dealing with the law are very vulnerable to handling that is not in accordance with the child's psychology or psychology. To decide the need for conflict with children to correct cases of crime / conflict with the law. Crimes are against the law Crimes are often followed up by experts Criminal prosecutions of double-edged double-edged swords or there are other debates saying the murder law will slice their own flesh wrong compilation in its application. the laws that children do often cause legal problems. Law enforcement officials are often absent in the action against lawsuits committed by children. Regulations taken in handling cases of children are often distorted and not involved by the authorities in the field, so it happens with children's rights and does not damage the child's future.